Incompatibilism and the Principle of Sufficient Reason in Kant’s Nova Dilucidatio - Aaron M Wells (Journal of Modern Philosophy)
The consensus is that in his 1755 Nova Dilucidatio, Kant endorsed broadly Leibnizian compatibilism, then switched to a strongly incompatibilist position in the early 1760s. I argue for an alternative, incompatibilist reading of the Nova Dilucidatio. On this reading, actions are partly grounded in indeterministic acts of volition, and partly in prior conative or cognitive motivations. Actions resulting from volitions are determined by volitions, but volitions themselves are not fully determined. This move, which was standard in medieval treatments of free choice, explains why Kant is so critical of Crusius’s version of libertarian freedom: Kant understands Crusius as making actions entirely random. In defense of this reading, I offer a new analysis of the version of the principle of sufficient reason that appears in the Nova Dilucidatio. This principle can be read as merely guaranteeing grounds for the existence of things or substances, rather than efficient causes for states and events. As such, the principle need not exclude libertarian freedom. Along the way, I seek to illuminate obscure aspects of Kant’s 1755 views on moral psychology, action theory, and the threat of theological determinism.